All‐Organic Battery Composed of Thianthrene‐ and TCAQ‐Based Polymers. Issue 5 (16th November 2016) - Wild, Andreas; Strumpf, Maria; Häupler, Bernhard; Hager, Martin D.; Schubert, Ulrich S.
Abstract : An all‐organic battery consisting of two redox‐polymers, namely poly(2‐vinylthianthrene) and poly(2‐methacrylamide‐TCAQ) is assembled. This all‐organic battery shows excellent performance characteristics, namely flat discharge plateaus, an output voltage exceeding 1.3 V, and theoretical capacities of both electrodes higher than 100 mA h g −1 . Both organic electrode materials are synthesized in two respective three synthetic steps using the free‐radical polymerization technique. Li‐organic batteries manufactured from these polymers prove their suitability as organic electrode materials. The cathode material poly(2‐vinylthianthrene) (3) displays a discharging plateau at 3.95 V versus Li + /Li and a discharge capacity of 105 mA h g −1, corresponding to a specific energy of about 415 mW h g −1 . The anode material poly(2‐methacrylamide‐TCAQ) (7) exhibits an initial discharge capacity of 130 mA h g −1, corresponding to 94% material activity. The combination of both materials results in an all‐organic battery with a discharge voltage of 1.35 V and an initial discharge capacity of 105 mA h g −1 (95% material activity). Abstract : An all‐organic battery exhibiting a discharge voltage of 1.35 V and an initial discharge capacity of 105 mA h g −1 is represented using the two organic redox‐polymers poly(2‐vinylthianthrene) and poly(2‐methacrylamide‐TCAQ). Both polymers can be synthesized in a straightforward two, respective three step synthetic procedure, also featuring superior material activity and stability in lithium‐organic batteries.